ONLINE EDUCATION: LEARNING OUTCOME, SUCCESS & CHALLENGES - Radin, Michael Alexander; Shlat, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This paper’s intents are to render the learning outcome, success and challenges that emerge in an online teaching and learning environment in comparison to the traditional face to face classroom environment. First of all, we will examine how the students acclimate to the new online digital learning atmosphere after the traditional face to face learning environment; what challenges and barriers the students encounter in a synchronous and in an asynchronous online learning environments? Second of all, we will focus on how professors adapt to the new digital online teaching styles and examine the new essential teaching innovations that arise in order to achieve and go beyond the expected learning outcomes; how to remit to the students’ challenges and retain the positive and engaging learning environment? In addition, our aims are to examine new pedagogical innovations that naturally emerge while responding to the students’ travails and to smoothly navigate them to achieve the expected learning outcomes.Furthermore, our paper’s intents are to portray how an online learning environment can attain more effective learning outcomes in comparison to the traditional face to face classroom environment; how to think beyond our horizons and to enhance the learning outcomes in a digital learning atmosphere while addressing the students’ challenges? Moreover, we will emphasize how the immediate graded feedback and students’ feedback serve as pertinent tools in achieving the learning outcome and inspires students to learn in an online atmosphere.